Consumer Legislation and Media Information Sources in India - Sharma, Vinod Kumar (Journal of Commerce and Trade, 2011)
The consumer has every right to reject any product or services rendered by any manufacturer in the market and can suggest them to produce goods of their choice. Indian Consumer are ignorant, illiterate and do no know the role of consumption vis-a-vis economic system as well as quality of life. When they are ignorant of their rights, they cannot know their responsibility as consumers. Consumers in the market find themselves deceived by wrong weights and measures, adulterated and substandard products causing great damages to health. Many constitutional provisions have been made by government to protect the consumers. Until and unless the consumers avail of these provisions, the protection of consumer becomes inevitable. There is a great need to make them aware of their rights and responsibilities in India.